Efecto de tres estrategias de manejo integrado sobre mosca blanca (Bemisia tabaci Gennadius) en cultivo de tomate (Solanum lycopersicum L.), en la Estación Experimental Zapotepamba - Jumbo Loaiza, Andreina de Jesús (2022)
Tomato cultivation in Ecuador has a lot importance since this product is part of the regular nutrition for families and also it has a great value for the agriculture of country. The commercialization volumes have a lot of importance in the national territory due to its multiple uses and its beneficial natural properties for human consumption, which have notably increased the demand for this vegetable. However, the crop is attacked by a wide range of pests, suchas the whitefly (Bemisia tabaci Gennadius), stands out and affects economically and which produces significant losses in national and provincial production. For this reason, it was intended to validate and apply an integrated analysis of the tomato whitefly. The investigation was carried out at the Zapotepamba Binational Technical Training Center, located in the Paltas canton, Loja province. It was established under a Completely Randomized Block Design, with five treatments and four repetitions. The variants examined for the pest were: number of adult insects per plant, incidence rate, and the variables evaluated in the plant were plant height, number of fruits and weight of fruits per tomato plant. The effect of the treatments on the dependent variants were evaluated using ANOVA and methods test (Tukey) (p=0.05). The results showed that in most of the variants statistically significant differences were found between treatments. However, the treatments of botanical extracts, biological control and chemical control, presented the best results in whitefly control. In general, the results of this work show that the different treatments produce a significant effect on the decrease of the population of Bemisia tabaci Gennadius. In regards to this research and based on the results, it is suggested to use three of the three components used (botanical extracts, biological extracts and chromatic traps) as a priority, in association, and as an alternative to the chemical control of whitefly in tomato crops (Solanum lycopersicum L.) of the zone. Keywords: Bemisia tabaci Gennadius, Solanum lycopersicum L, botanical extracts, biological control, color traps, chemical control, integrated analysis.